Identification and characterisation of novel transcripts in mouse oocytes and embryos - Kraváriková, Karolína (Jihočeská univerzita, 2020)
The primary goal of this bachelor thesis was to identify novel transcripts in mouse oocytes and preimplantation embryos, analyse their expression profile, protein coding potential, the activity of transposable elements as promoters of such transcripts, in order to select candidate transcripts for functional analysis of their roles in mammalian development.
Identification and characterisation of novel transcripts in mouse oocytes and embryos
Keywords: genetics; genetics